LAJU KONVERSI LAHAN SAWAH MENJADI PERKEBUNAN SAWIT DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA SERTA DAMPAKNYA TERHADAP PRODUKSI PADI DI KABUPATEN KAMPAR, RIAU - Fahri, Anis; M. Kolopaking, Lala; Budiman.Hakim, Dedi (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2014)
Conversion Rate of Rice Field to Palm Oil Plantation, the Affected Factors and Its Impact to Rice Production in Kampar District, Riau. Kampar district is a center of rice production area in Riau Province and since ten years ago had been being conversed to palm oil plantation. This study aimed: (1) to identify the rate of land conversion, (2) to analyze factors that influence the conversion of paddy fields at the farm level, (3) to identify impact of paddy field conversion on rice production. The study was conducted in Kampar district from April to December 2013 using survey design and involving 60 farmers as respondent that consisted of 30 paddy farmers in Kampar Sub District and 30 farmers in Tambang Sub District who undertook paddy field conversion to palm oil plantations. Analyzing the data used multiple linear regressions. The results of landsat analysis from 2002 to 2010 showed a decreased occurred paddy field area by 1955.79 ha (21.77%) (from 8,984 ha to 7028.21 acres). The factors which significantly influenced paddy field conversion were: (1) reduction in paddy farming income, (2) an increase in palm oil farming income, (3) irrigation constraints, and (4) the lack of knowledge regarding the regulation of paddy field. Paddy field conversion during the period of 2002-2010 was estimated on causing the loss of 9,192 t of grain, which was, equivalent to 5,767 t of rice per years. Key words: Land conversion, palm oil, paddy field, Kampar District Kabupaten Kampar merupakan sentra produksi beras di Provinsi Riau yang dalam kurun waktu sepuluh tahun terakhir terjadi konversi lahan sawah. Penelitian ini bertujuan: (1) mengidentifikasi laju konversi lahan sawah, (2) menganalisis faktor-faktor yang mempengaruhi konversi lahan sawah di tingkat petani, (3) mengidentifikasi dampak konversi lahan sawah terhadap ketahanan pangan. Penelitian dilaksanakan di Kabupaten Kampar Provinsi Riau dari bulan April hingga Desember 2013 menggunakan rancangan survey yang melibatkan 60 petani responden, terdiri dari 30 petani padi di Kecamatan Kampar dan 30 petani yang melakukan konversi lahan sawah ke perkebunan kelapa sawit di Kecamatan Tambang. Analisis data mengggunakan regresi linear berganda. Hasil interpretasi data citra landsat 2002-2010 menunjukkan terjadi penyusutan lahan sawah seluas 1.955,79 ha (21,77%) dari 8.984 ha menjadi 7.028,21 ha. Faktor-faktor yang diduga secara signifikan mempengaruhi konversi lahan sawah di tingkat petani adalah: (1) penurunan pendapatan usahatani padi, (2) peningkatan pendapatan usahatani kelapa sawit, (3) kendala irigasi dan (4) kurangnya pengetahuan tentang kebijakan larangan konversi lahan sawah. Konversi lahan sawah selama periode 2002 - 2010 diperkirakan telah menyebabkan hilangnya 9.192 t gabah kering giling atau setara dengan 5.767 t beras/tahun. Kata kunci: Konversi lahan, kelapa sawit, padi sawah, Kabupaten Kampar